NH4Cl-induced metabolic acidosis increases the abundance of HCO3− transporters in the choroid plexus of mice - Johnsen, Laura Øllegaard; Sigad, Ahmed; Friis, Kathrine Abildskov; Berg, Peder Matzen; Damkier, Helle Hasager (Frontiers in Physiology, 2024)
Regulation of cerebrospinal fluid (CSF) pH and brain pH are vital for all brain cells. The acute regulation of CSF pH is dependent on the transport of HCO3 -across the choroid plexus in the brain ventricles. Acute regulation in response to acidosis is dependent on H + export and HCO3 -import across the plasma membrane. Acute regulation in response to alkalosis is dependent on HCO3 -export across the plasma membrane. The objective of the study was to investigate the contribution of the Na +dependent HCO3 -transporters, Ncbe, NBCn1, and NBCe2 to CSF pH regulation during chronic metabolic acidosis in mice. To induce metabolic acidosis, mice received 0.28 M ammonium chloride (NH4Cl) in the drinking water for three, five, or seven days. While in vivo, CSF pH measurements did not differ, measurements of CSF [HCO3 -] revealed a significantly lower CSF [HCO3 -] after three days of acid-loading. Immunoblotting of choroid plexus protein samples showed that the abundance of the basolateral Na + / HCO3 -transporter, NBCn1, was significantly increased. This was followed by a significant increase in CSF secretion rate determined by ventriculo-cisternal perfusion. After five days of treatment with NH4Cl, CSF [HCO3 -] levels were normalized. After the normalization of CSF [HCO3 - ], CSF secretion was no longer increased but the abundance of the basolateral Na + -dependent HCO3 - transporters Ncbe and NBCn1 increased. The luminal HCO3 -transporter, NBCe2, was unaffected by the treatment.In conclusion, we establish that 1) acidotic conditions increase the abundance of the basolateral Na +dependent HCO3 -transporters in the choroid plexus, 2) NH4Cl loading in mice lowers CSF [HCO3 -], and 3) leads to increased CSF secretion likely caused by the increased capacity for transepithelial transport of Na + and HCO3 -in the choroid plexus.